2023
DOI: 10.1021/acs.joc.2c02906
|View full text |Cite
|
Sign up to set email alerts
|

Ynamides in Radical Reactions: A Route to Original Persubstituted 2-Aminofurans

Abstract: Mn(OAc) 3 /Cu(OAc) 2 -mediated reaction between ynamides, derived from oxazolidone or 3-methylindole carboxylate, and cyclic α-dicarbonyl radicals led to the one-pot synthesis of 2aminofurans. The transformation involves addition of the α-dicarbonyl radical to ynamide, oxidation to ketene-iminium, and polar cyclization steps to provide original persubstituted 2-aminofurans in good to excellent yields. This work represents the first radical route for the synthesis of furans from ynamides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
0
0
Order By: Relevance
“…For some years now, our group has been interested in the involvement of ynamides in free-radical transformations . In the course of our investigations, we found that upon activation under irradiation at 365 nm at room temperature, in the absence of any additives, N -sulfonyl ynamides 3 could be converted into α-sulfonyl amides 4 in high yield through a N to C migration of the sulfonyl group (Scheme d).…”
mentioning
confidence: 99%
“…For some years now, our group has been interested in the involvement of ynamides in free-radical transformations . In the course of our investigations, we found that upon activation under irradiation at 365 nm at room temperature, in the absence of any additives, N -sulfonyl ynamides 3 could be converted into α-sulfonyl amides 4 in high yield through a N to C migration of the sulfonyl group (Scheme d).…”
mentioning
confidence: 99%